2018
DOI: 10.1016/bs.irn.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Placebo Effects in Patients With Pain Disorders

Abstract: The analgesic placebo effect is well documented by numerous studies. Many important influencing factors, however, are yet to be discovered. In the arena of placebo effects and clinical implications, expectancies play a central role. Expectancies are shaped by processes of classical and social learning as well as verbal instructions and are strongly related to emotional factors. Expectancies trigger a cascade of endogenous opioids and nonopioids, which alter the experience of pain. For clinical application it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 85 publications
(125 reference statements)
0
57
0
5
Order By: Relevance
“…Even though half of the included studies did not clarify the status of patients' analgesic response to medications, the neuromodulation effects seem to be higher on the intractable DPN population. It has been reported that patients with intractable pain disorders have less treatment expectancy and placebo effect 70 . Consequently, we can argue that our pooled estimated effect is less likely to be affected by the placebo effect of the sham intervention.…”
Section: Sources Of Heterogeneity and Potential Explanations Accordimentioning
confidence: 99%
“…Even though half of the included studies did not clarify the status of patients' analgesic response to medications, the neuromodulation effects seem to be higher on the intractable DPN population. It has been reported that patients with intractable pain disorders have less treatment expectancy and placebo effect 70 . Consequently, we can argue that our pooled estimated effect is less likely to be affected by the placebo effect of the sham intervention.…”
Section: Sources Of Heterogeneity and Potential Explanations Accordimentioning
confidence: 99%
“…These findings are among the first attempts to outline the clinical relevance of shaping patients’ expectancies (Darnall & Colloca, 2018; Klinger, Stuhlreyer, Schwartz, Schmitz, & Colloca, 2018) and to use dose-extending placebos along with pharmacological conditioning as a potential pain management tool to taper opioids (Colloca, Enck, & DeGrazia, 2016; Colloca & Howick, 2018). …”
mentioning
confidence: 91%
“…There is increasing consensus that clinicians can actively set positive patients’ expectations (Darnall & Colloca, 2018; Glare, Fridman, & Ashton-James, 2018; Klinger et al, 2018). Educating patients about pain treatments and their effects can strengthen their overall pain reduction, coping, and resilience skills.…”
mentioning
confidence: 99%
“…The analgesic placebo effect has been well documented. 12 In the area of placebo effects, expectations play a major role, triggering a cascade of endogenous opioids and non-opioids, and altering the experience of pain. 12 For this reason, the field of anaesthesiology and pain research is likely biased if blinding is not used adequately.…”
Section: Introductionmentioning
confidence: 99%